K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

4 tháng 12 2021

3x+1-1=26

=>3x+1=26+1

=>3x+1=27

=>3xx3=27

=>3x=27:3          =>3x=9     =>x=2

19 tháng 11 2021

\(3^{x+1}-2.3^x=243\\ \Rightarrow3^x.3-2.3^x=243\\ \Rightarrow3^x=3^5\\ \Rightarrow x=5\)

19 tháng 11 2021

\(d.3^{x+1}-2.3^x=243\)

2 tháng 5 2023

\(\dfrac{1}{2}\left(x-2\right)+\dfrac{1}{3}\left(2-x\right)=x\\ \Leftrightarrow\dfrac{1}{2}\left(x-2\right)-\dfrac{1}{3}\left(x-2\right)=x\\ \Leftrightarrow\left(x-2\right).\left(\dfrac{1}{2}-\dfrac{1}{3}\right)=x\\ \Leftrightarrow\left(x-2\right).\left(\dfrac{3-2}{6}\right)=x\\ \Leftrightarrow\left(x-2\right).\dfrac{1}{6}=x\\ \Leftrightarrow\dfrac{1}{6}x-\dfrac{1}{3}-x=0\\ \Leftrightarrow\left(\dfrac{1}{6}-1\right)x=\dfrac{1}{3}\\ \Leftrightarrow\left(\dfrac{1-6}{6}\right)x=\dfrac{1}{3}\\ \Leftrightarrow\dfrac{-5}{6}x=\dfrac{1}{3}\\ \Leftrightarrow x=\dfrac{1}{3}:\left(-\dfrac{5}{6}\right)\\ \Leftrightarrow x=-\dfrac{2}{5}\)

Vậy \(x=-\dfrac{2}{5}\)

2 tháng 5 2023

x= \(\dfrac{7\pm\sqrt{37}}{3}\) nha

 

27 tháng 4 2022

3 x 6 + 3 x 70 + 24 x 3

= 3 x (6 + 70 + 24)

= 3 x 100

= 300

27 tháng 4 2022

   3 x 6 + 3 x 70 + 24 x 3

= 3 x (6 + 70 + 24)

= 3 x 100 = 300

 

15 tháng 8 2021

| x-2/3| = 1/3+2/5

             = 11/15

=> x-2/3=11/15          hoặc x-2/3=-11/15

            x= 7/5                      x       = -1/15

k cho mk nha

\(\left|x-\frac{2}{3}\right|-\frac{2}{5}=\frac{1}{3}\)

\(\Rightarrow\left|x-\frac{2}{3}\right|=\frac{1}{3}+\frac{2}{5}=\frac{11}{15}\)

\(\Rightarrow\orbr{\begin{cases}\Rightarrow x-\frac{2}{3}=\frac{11}{15}\\x-\frac{2}{3}=\frac{-11}{15}\end{cases}}\)

\(\Rightarrow\orbr{\begin{cases}\Rightarrow x=\frac{7}{15}\\x=\frac{-1}{15}\end{cases}}\)

28 tháng 9 2021

\(\left(3-x\right)\left(x+1\right)-\left(2.x\right)\left(x+2\right)-3\)

\(=3x+3-x^2-x-2x^2-4x-3=-3x^2-2x\)

DT
27 tháng 11 2023

\(\dfrac{x^3+8}{x^2+2x+1}.\dfrac{x^2+3x+2}{1-x^2}\left(x\ne\pm1\right)\\ =\dfrac{x^3+2^3}{\left(x+1\right)^2}.\dfrac{\left(x^2+x\right)+\left(2x+2\right)}{1^2-x^2}\\ =\dfrac{\left(x+2\right)\left(x^2-2x+4\right)}{\left(x+1\right)^2}.\dfrac{x\left(x+1\right)+2\left(x+1\right)}{\left(1-x\right)\left(1+x\right)}\\ =\dfrac{\left(x+2\right)\left(x^2-2x+4\right)}{\left(x+1\right)^2}.\dfrac{\left(x+2\right)\left(x+1\right)}{\left(1-x\right)\left(x+1\right)}\\ =\dfrac{\left(x+2\right)^2\left(x^2-2x+4\right)}{\left(1-x\right)\left(x+1\right)^2}\)